Degradation characteristics of porous Fe-Mn-C alloys obtained by sintering-dissolution process (SDP) for metallic bone scaffold - Pratesa, Yudha; Almira Larasati,; Harjanto, Sri; Suharno, Bambang; Myrna Ariati, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Porous degradable metal is a promising material for hard-tissue scaffold application. It offers better mechanical properties than polymer and easier cell proliferation. However, the corrosion process in the porous metallic implant usually causes toxicity on patient. Therefore, corrosion process is the key for the development of the alloy. The previous study has successfully formed a porous Iron-35%Manganese-1%Carbon (Fe-35Mn-1C) alloy using Potassium carbonate (K2CO3) as foaming agent with powder metallurgy process. This study focused on the degradation behavior and phase analysis of Fe-Mn-C product by polarization test in ringer solution, Atomic Absorption Spectrometry (AAS), X-Ray Diffraction, and Energy Dispersive Spectroscopy. This process resulted in nonmagnetic Austenitic phase that is beneficial for MRI application. The result showed that Fe-Mn-C alloy with foaming structure is suitable for degradable biomaterials. The density of the product is 3.2 gr/cm3, which is only half of the bulk material. The degradation rate of the metals also increases to 6 mm/year, but the maximum ion released is still under the limit in terms of toxicity against human.